1986
DOI: 10.1099/00221287-132-6-1665
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Recovery of Buoyancy by Microcystis

Abstract: Colonies of Microcystis in Abbots Pool, Avon, UK, were found to regulate their buoyancy according to light (photon flux density). The autumnal decline of the population was associated with an increase in the proportion of colonies that were non-buoyant, and with declining temperatures in the pond. Non-buoyant colonies taken from the pond regained buoyancy in the dark rapidly at 20 "C but only slowly at 12 "C and below. A laboratory strain of Microcystis behaved in a similar manner. Comparisons of the behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 19 publications
2
56
0
1
Order By: Relevance
“…M. aeruginosa possesses a physiological and biochemical flexibility that enhances its chances of survival. In spring, increased viability allows benthic M. aeruginosa to remain buoyant because of their ability to grow by producing proteins at the expense of carbohydrate (these abilities are sensitive to the effects of temperature) (Thomas & Walsby 1986). As a consequence, in spring, when temperatures rise, more specifically when hypolimnetic temperature exceeds 8°C, a part of the benthic M. aeruginosa colonies could return to the water column (Latour 2002).…”
Section: Frequency Of Dividing Cells (Experimental Method)mentioning
confidence: 99%
See 2 more Smart Citations
“…M. aeruginosa possesses a physiological and biochemical flexibility that enhances its chances of survival. In spring, increased viability allows benthic M. aeruginosa to remain buoyant because of their ability to grow by producing proteins at the expense of carbohydrate (these abilities are sensitive to the effects of temperature) (Thomas & Walsby 1986). As a consequence, in spring, when temperatures rise, more specifically when hypolimnetic temperature exceeds 8°C, a part of the benthic M. aeruginosa colonies could return to the water column (Latour 2002).…”
Section: Frequency Of Dividing Cells (Experimental Method)mentioning
confidence: 99%
“…Indeed, a threshold temperature may exist below which cell growth is reduced. Thomas & Walsby (1986) indicated that at 8°C the rates of protein synthesis in the dark by benthic cyanobacteria were greatly reduced. Moreover, lower temperature may have been critical, and no significant increases of protein synthesis were recorded for M. aeruginosa until the temperature had exceeded 7°C (Càceres & Reynolds 1984).…”
Section: Frequency Of Dividing Cells (Experimental Method)mentioning
confidence: 99%
See 1 more Smart Citation
“…8). For this demonstration, we quantified resistance as mean epilimnetic water temperature, based on Thomas and Walsby's (1986) finding that Microcystis buoyancy regulation is severely impaired at low winter temperatures, and on the general notion that growth in Microcystis is temperature dependent (Robarts and Zohary 1987). Resilience was approximated by an index of water column P concentrations and estimated ''overwintering seed stock'' of Microcystis in spring, where the seed stock was assumed proportional to the maximum Microcystis biomass prior to the bloom crash.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the in situ observation that the population density of Microcystis species in the water increased with water temperature. The upward movement of Microcystis species is obviously regulated by cell buoyancy, and some researchers have suggested a positive effect of temperature on the recovery of buoyancy in Microcystis colonies or an increase in the number of buoyant colonies (Thomas & Walsby 1986, Tsujimura et al 2000, Brunberg & Blomqvist 2003, Verspagen et al 2005. Therefore, Microcystis colonies in the sediment are probably stimulated to become active quickly in response to an increase in temperature.…”
Section: Discussionmentioning
confidence: 99%